2012
DOI: 10.4314/ajtcam.v9i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid compounds identified in <i>Alchemilla l.</i> species collected in the North-eastern Black sea region of Turkey

Abstract: This study identified flavonoid glycosides in species of the genus Alchemilla, A. procerrima, A. stricta, A. hirtipedicellata and A. sericata. A. procerrima is an endemic species for Turkey. After detailed investigation, flavonoid compounds of the species were identified for the first time. In this study, flavonoid compounds were determined by using two different chromatography techniques, TLC and HPLC. The following flavonoid compounds were identified from the Alchemilla species studied. They are as follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
(4 reference statements)
2
22
0
1
Order By: Relevance
“…Alchemilla species (Rosaceae) has been used for medicinal properties for centuries, and this genus is quite common all over the world. Especially Alchemilla vulgaris ‘Lady's mantle’ is represented as ‘Herba Alchemillae’ in the European Pharmacopoeia . Alchemilla is used for astringent, anti‐hemorrhoidal, and anti‐diarrheal activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alchemilla species (Rosaceae) has been used for medicinal properties for centuries, and this genus is quite common all over the world. Especially Alchemilla vulgaris ‘Lady's mantle’ is represented as ‘Herba Alchemillae’ in the European Pharmacopoeia . Alchemilla is used for astringent, anti‐hemorrhoidal, and anti‐diarrheal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Especially Alchemilla vulgaris 'Lady's mantle' is represented as 'Herba Alchemillae' in the European Pharmacopoeia. [8][9] Alchemilla is used for astringent, anti-hemorrhoidal, and anti-diarrheal activity. In traditional medicine, infusion of this plant has been used externally for treatment of stomatitis and wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Among the isolated compounds; catechin was previously isolated from A. mollis [12] and A. speciosa [36], tiliroside was isolated from A. achtarowii [13] and A. mollis [37], while miquelianin and guaiaverin were isolated from A. xanthochlora [14,38] and A. achtarowii [13]. As well as hyperoside was reported to be present in A. procerrima, A. hirtipedicellata, A. sericata [11]. However, catechin dimer; procyanidin B3 is being reported for the first time from the genus Alchemilla.…”
Section: Figure 1 Structures Of Compounds 1-7 Isolated From a Barbamentioning
confidence: 99%
“…Moreover, calendula has healing and antiseptic properties with actions that are sudorific and analgesic, affect the bile duct, are antiinflammatory, antiviral and anti-emetic, and tone the skin with vasodilation [15]. Kaya et al (2012) also indicated that flavonoids captured the interest of scientists from many different disciplines because of their structural diversity, biological and ecological significance in systematic, and health-promoting and anti-cancer properties [16]. Yarrow (Achillea millefolium L.) also traditionally has been used as an abortifacient, emmenagogue, contraceptive, and for stimulating uterine contractions.…”
Section: Introductionmentioning
confidence: 99%